2012 National Turfgrass Evaluation Program Tall Fescue Test: 2016 Data - L. Parsons; Michael J. Shelton; M. Kennelly; J. Griffin; J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2017)
Research efforts to improve cultivar quality include selecting for stress tolerance and disease resistance as well as finer leaf texture, a rich green color, and better sward density. Several cultivars included in the 2012 National Turfgrass Evaluation Program Tall Fescue Test performed well and showed good brown patch resistance in south central Kansas during the 2016 growing season.
Keywords: brown patch; resistance; tall fescue; transition zone; National Turfgrass Evaluation Program; NTEP